The Determinants of Capital Structure on China-Listed Construction Companies - Chandra Setiawan; Qu Yumeng (President University Press, 2021)
Contruction companies in China debt to asset ratio around 76.16 % to 82.67% compared to other countries in average below 40%. Therefore, the objective of this research is to find out the determinants of the capital structure of listed construction companies in China. By employing the panel multiple regression model to meet the research objective. Through purposive sampling technique 10 listed companies in the construction industry from 2012 to 2019 are selected as samples, so there are 80 observations sample. The variable used to proxy capital structure is total debt ratio, and the independent variables are profitability, asset tangibility, firm size, growth opportunities, non-debt tax shield, interest rate and inflation rate. Among the independent variables been tested, the results reveal that five independent variables, except non-debt tax shield and inflation rate have a significant impact toward capital structure. Interest rate is the most significant influence variable. Finally, this research puts forward relevant suggestions for the optimization of the company's capital structure.